Эндодонтическое лечение в одно посещение: современные стандарты. Часть V (LLC "Endo Press", 2020)
The article discusses the importance of three-dimensional obturation of root canals. However, mentioned that this is not the only criterion for obtaining good long term results. For longterm success crown tightness of the tooth is more important than the apical one. We consider the conditions of treatment of teeth with endopatology, various methods of gutta-percha use.